Prevalence and associated factors of anemia among adolescent girls attending high schools in Dembia District, Northwest Ethiopia, 2017 - Kedir Abdela Gonete; Amare Tariku; Sintayehu Daba Wami; Terefe Derso (Archives of Public Health, 2018)
Abstract Introduction Anemia is a global public health problem affecting both developing and developed countries. In Ethiopia, Adolescent girls are more vulnerable to anemia because of gender norms can leave girls disproportionately impacted by food insecurity, increased iron requirements related to their rapid growth, and menstrual loss. However, evidence on the problem is scarce because it has not been given due attention in Ethiopia. Therefore, this study assessed the prevalence and associated factors of anemia among late adolescent girls attending high schools in Dembia District, northwest Ethiopia. Methods A school based cross-sectional study was conducted in Dembia District from March 1 to April 30/ 2017. Out of the randomly selected three high schools, 462 adolescents were included using the simple random sampling technique. A Standardized structured questionnaire was used to collect data. Capillary blood samples were drawn from adolescents using a portable Hb201+ instrument to measure hemoglobin. A bivariate and multivariable binary logistic regression analyses were employed to identify factors associated with anemia. Adjusted Odds Ratio (AOR) with a corresponding 95% Confidence Interval (CI) was computed to show the strength of associations. Results The overall prevalence of anaemia among adolescent girls was 25.5%, (95%CI, 21.4, and 29.2). Of the total anemic adolescents, 109(92.4%) had mild anaemia, while 7(5.9%) and 2(1.7%) were found with moderate and severe anaemia, respectively. Dietary diversity score ((AOR =4.2(95% CI;1.7, 10.5)), household food security status ((AOR = 4.1(95% CI; 1.3, 13.2)), living status of adolescents with either of the two parents((AOR = 2;(95%CI;1.14,3.6)) and guardians ((AOR = 2.4;(95% CI;1.02,5.6)) showed statistically significant association with anemia. Conclusion Anemia is a moderate public health problem in Dembia District. Dietary diversity score, household food security status, and living status of adolescents were the key determinants of anemia. Therefore, the government should focus on preventing food insecurity with increasing productivity to improve dietary diversification of the adolescent girls. Trial registration Retrospectively registered.